2022
DOI: 10.1039/d1tc05304c
|View full text |Cite
|
Sign up to set email alerts
|

Flexible capacitive pressure sensors for wearable electronics

Abstract: Flexible pressure sensors have attracted more and more attention recently due to their broad applications, such as electronic skin and wearable electronics for health monitoring. Among them, capacitive flexible pressure...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
81
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(82 citation statements)
references
References 104 publications
1
81
0
Order By: Relevance
“…Intriguingly, emerging data suggest that an intricate balance of formylation and deformylation is crucial for membrane-associated cellular functions. A previous study (Ranjan et al, 2017) and our recent work (Yang et al, 2022) demonstrated that a significant fraction of the membrane and secretory proteome is resistant to deformylation under physiological conditions, suggesting that fMet retention on some membrane and secretory proteins may be necessary. Our current work showed that the deformylation of a distinct set of the proteome is crucial for maintaining the proper structure and function of the bacterial membrane.…”
Section: Discussionmentioning
confidence: 88%
“…Intriguingly, emerging data suggest that an intricate balance of formylation and deformylation is crucial for membrane-associated cellular functions. A previous study (Ranjan et al, 2017) and our recent work (Yang et al, 2022) demonstrated that a significant fraction of the membrane and secretory proteome is resistant to deformylation under physiological conditions, suggesting that fMet retention on some membrane and secretory proteins may be necessary. Our current work showed that the deformylation of a distinct set of the proteome is crucial for maintaining the proper structure and function of the bacterial membrane.…”
Section: Discussionmentioning
confidence: 88%
“…Generally, conventional biomedical equipment is rigid and cannot be fitted closely at the monitoring site, therefore resulting in inaccurate monitoring data and making the patient uncomfortable while wearing a device. Flexible sensors are easily fitted onto human skin due to their great flexibility and stretchability [2,[110][111][112][113]. These sensors possess…”
Section: Flexible Sensors As Biomedical Devicesmentioning
confidence: 99%
“…Generally, conventional biomedical equipment is rigid and cannot be fitted closely at the monitoring site, therefore resulting in inaccurate monitoring data and making the patient uncomfortable while wearing a device. Flexible sensors are easily fitted onto human skin due to their great flexibility and stretchability [2,[110][111][112][113]. These sensors possess high sensitivity, stretchability, and quick response time, due to which they would be a sustainable and ideal choice for future applications in the biomedical field such as pressure detection, sound variation, vital sign monitoring, and pulse monitoring (Figure 5).…”
Section: Flexible Sensors As Biomedical Devicesmentioning
confidence: 99%
“…57 The pressure sensor rearranges the electrostatic potential of internal ions, causing changes in electrical resistance, which is based on the piezoresistive effect of the hydrogel. 58 The temperature sensor utilizes the monotonic increase of the electrical conductivity of the hydrogel with temperature to monitor the temperature change in real-time. 54 For the humidity hydrogel sensor, the hydrophilic groups on hydrogels/organohydrogels can absorb and desorb moisture from the surrounding environment upon relative humidity variations, which can change the electrical properties.…”
Section: Introductionmentioning
confidence: 99%